2010
DOI: 10.1007/s00726-010-0525-3
|View full text |Cite
|
Sign up to set email alerts
|

Proline metabolism and transport in plant development

Abstract: Proline fulfils diverse functions in plants. As amino acid it is a structural component of proteins, but it also plays a role as compatible solute under environmental stress conditions. Proline metabolism involves several subcellular compartments and contributes to the redox balance of the cell. Proline synthesis has been associated with tissues undergoing rapid cell divisions, such as shoot apical meristems, and appears to be involved in floral transition and embryo development. High levels of proline can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
225
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(240 citation statements)
references
References 176 publications
(170 reference statements)
8
225
2
5
Order By: Relevance
“…Therefore, our research shows that saline stress induced during the growth of sunflower plants immediately after germination, causes the accumulation of proline in the plumules in response to the stress factor. In this context, other studies have also shown that the accumulation of free proline in saline stress conditions is an osmotic control reaction of sunflower plants (Lehmann et al, 2010;Khalil, 2017, Reddy et al, 2004;Saleh and Madany, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, our research shows that saline stress induced during the growth of sunflower plants immediately after germination, causes the accumulation of proline in the plumules in response to the stress factor. In this context, other studies have also shown that the accumulation of free proline in saline stress conditions is an osmotic control reaction of sunflower plants (Lehmann et al, 2010;Khalil, 2017, Reddy et al, 2004;Saleh and Madany, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…A prolina, em condições de estresses abióticos, pode ser uma molécula chave de sinalização capaz de desencadear múltiplas respostas que fazem parte do processo de aclimatação. O acúmulo de prolina, além de estar relacionado com o ajustamento osmótico pode contribuir para a estabilização de membranas e proteínas; promover a eliminação de radicais livres; atuar na sinalização celular; participar do equilíbrio de oxirredução e na indução da expressão de genes (Lehmann et al, 2010).…”
Section: Introductionunclassified
“…However the expansion of oxidative stress research has given many new insights into the role of proline in plants. Today it is clear that proline is a multifunctional amino acid [1][2][3][4] with many metabolism pathways being revealed. [5][6][7] The proline concentrations of cells, tissues and plant organs are regulated by the interplay of biosynthesis, degradation and intra-as well as intercellular transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The proline concentrations of cells, tissues and plant organs are regulated by the interplay of biosynthesis, degradation and intra-as well as intercellular transport processes. 1,2 There are two different precursors for proline biosynthesis in plants. The first pathway uses glutamate which is converted to proline by two successive reductions catalyzed by Δ 1 -pyrroline-5-carboxylate synthetase (P5CS) and pyrroline-5-carboxylate reductase (P5CR), respectively, both using NADPH as a cofactor.…”
Section: Introductionmentioning
confidence: 99%